2012
DOI: 10.1126/science.1223702
|View full text |Cite
|
Sign up to set email alerts
|

A Killer-Protector System Regulates Both Hybrid Sterility and Segregation Distortion in Rice

Abstract: Hybrid sterility is a major form of postzygotic reproductive isolation that restricts gene flow between populations. Cultivated rice (Oryza sativa L.) consists of two subspecies, indica and japonica; inter-subspecific hybrids are usually sterile. We show that a killer-protector system at the S5 locus encoded by three tightly linked genes [Open Reading Frame 3 (ORF3) to ORF5] regulates fertility in indica-japonica hybrids. During female sporogenesis, the action of ORF5+ (killer) and ORF4+ (partner) causes endop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
254
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(262 citation statements)
references
References 38 publications
5
254
0
3
Order By: Relevance
“…Kubo et al (2008) showed that hybrid male sterility is caused by epistasis between two novel genes, S24 and S35, on rice chromosomes 5 and 1. Similar results have also been found in Drosophila (Chang and Noor, 2010), alfalfa (Li et al, 2011), rice (Xie and Chen, 2012;Yang et al, 2012) and Arabidopsis lyrata (Leppälä et al, 2013). Thus, the Dobzhansky-Muller model, in which hybrid inviability is assumed to be caused by epistasis (Dobzhansky, 1936;Muller, 1942), has been widely accepted.…”
Section: Introductionsupporting
confidence: 65%
“…Kubo et al (2008) showed that hybrid male sterility is caused by epistasis between two novel genes, S24 and S35, on rice chromosomes 5 and 1. Similar results have also been found in Drosophila (Chang and Noor, 2010), alfalfa (Li et al, 2011), rice (Xie and Chen, 2012;Yang et al, 2012) and Arabidopsis lyrata (Leppälä et al, 2013). Thus, the Dobzhansky-Muller model, in which hybrid inviability is assumed to be caused by epistasis (Dobzhansky, 1936;Muller, 1942), has been widely accepted.…”
Section: Introductionsupporting
confidence: 65%
“…S19-S23 and Table S36). We further examined the other two ORFs (ORF3 and ORF4) at this locus that work with ORF5 to form a killer-protector system (46). In the high-quality assemblies of S5 orthologous genomic regions for all five newly sequenced genomes, our results showed that ORF3 was fragmented and ORF4 was not detected in both GLA and BAR genomes.…”
Section: Resultsmentioning
confidence: 84%
“…In rice in particular, a number of gamete killers have been described in crosses between cultivated rice (O. sativa) and its wild relatives (Sano 1990;Hu et al 2006;Garavito et al 2010), or between O. sativa subspecies (Oka 1974;Zhang et al 2006). The genes underlying two of the latter have been identified (Chen et al 2008;Long et al 2008;Yang et al 2012). Gamete killers are also found in wild species, as in the interspecific cross between Mimulus guttatus and M. nasutus (Fishman and Saunders 2008), and, at the intraspecific level, in some populations of the dioecious Silene latifolia (Taylor and Ingvarsson 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In both of these BDM interactions, a particular combination of alleles present at the two loci is deleterious at the haploid stage, leading to the production of deficient pollen grains in the hybrid plant. In addition, at least two examples of one-locus hybrid sterility have been reported in rice (Long et al 2008;Yang et al 2012). In these cases, hybrid sterility results from the abortion of the gametophytes (pollen grains in one case, embryo sacs in the other) that carry one of the parental alleles, when in the presence of the other allele in the hybrid.…”
mentioning
confidence: 99%